The prevalence of pressure ulcers in community‐dwelling older adults: A study in an Indonesian city. Issue 2 (15th February 2019) - Sari, Sheizi P.; Everink, Irma H.; Sari, Eka A.; Afriandi, Irvan; Amir, Yufitriana; Lohrmann, Christa; Halfens, Ruud J.; Schols, Jos M.
Abstract : The objectives of this study were to investigate the prevalence and the characteristics of pressure ulcers (PU) in community‐dwelling older adults in Indonesia, including specific characteristics of the PU patients and their use of formal and informal care. A cross‐sectional design was used for the study, with 325 participants aged 60 years or older, randomly chosen from the general community. The overall PU prevalence and the PU prevalence excluding category 1 were 10.8% (95% confidence interval [CI], 5.8‐15.8) and 5.2% (95% CI 0.2‐10.2), respectively. Category 1 PUs were mostly (34.3%) located on knees and toes, while category 2 and higher PUs were mostly (70.4%) located on the shoulder, sacrum, and hip. The main factors that contributed strongly to PUs among older adults in the community were the degree of physical activity, problems with sensory perception, and having a history of stroke. None of the participants with a PU received wound care or information about PUs from formal caregivers and only 11.4% received wound care from family caregivers. This study shows that pressure ulcers in community‐dwelling older adults in Indonesia are a relevant and largely unaddressed problem. Developing an intervention program to manage the PU problem in the community is recommended.